Higher order risk attitudes and prevention under different timings of loss - Takehito Masuda; Eungik Lee (Osaka University, Institute of Social and Economic Research (ISER), 2018)
This paper provides experimental evidence of the role of higher order risk attitudes - especially prudence - in prevention behavior. Prudence, under an expected utility framework, increases (decreases) self-protection effort compared to the risk neutral level when the risk of losing part of an income exists in a future (the same) period. Motivated by these predictions that give the exact test on prudence, an experiment was designed where subjects go through higher order risk attitude elicitation and make a self-protection decision. In contrast to expected utility theory, the observed efforts are less than the risk neutral level, regardless of the timing of loss. This violation of expected utility predictions could be explained by probability weighting.
Keywords: C91; C92; D81; E21; 330; Higher order risk attitudes; Prudence; Prevention; Timing of loss; Probability weighting